Mental health plans and policies across the WHO European region - Guerrero, Zoe; Kågström, Anna; Aliev, Akmal; Tomášková, Hana; Yon, Yongjie; Lazeri, Ledia; Reinap, Marge; Redlich, Cassie; Tijerino Inestroza, Ana Maria; Maurer, Jason; Winkler, Petr (Global mental health (Cambridge, England), 2024)
Evidence is scarce in terms of tracking the progress of implementation of mental healthcare plans and policies (MHPPs) in Europe, we aimed to map and analyze the content of MHPPs across the WHO European region. We collected data from the WHO Mental Health Atlas 2011, 2017 and 2020 to map the development of MHPPs in the region. We contacted 53 key informants from each country in the European region to triangulate the data from WHO Mental Health Atlases and to obtain access to the national mental health plans and policies. We analyzed the content of MHPPs against the four major objectives of the WHO Comprehensive Mental Health Action Plan, and we also focused on the specificity and measurability of their targets. The number and proportion of countries which have their own MHPPs has increased from 30 (52%) to 43 (91%) between 2011 and 2020. MHPPs are generally in line with the WHO policy, aiming to strengthen care in the community, expand mental health promotion and illness prevention activities, improve quality of care, increase intersectoral collaboration, build workforce and system capacity, and improve adherence to human rights. However, specific, and measurable targets as well as a description of concrete steps, responsibilities and funding sources are mostly missing. They often contain very little information systems, evidence and research, and mostly lack information on evaluating the implementation of MHPPs. Progress has been made in terms of the development of MHPPs in the WHO Europe. However, MHPPs are often lacking operationalization and appropriate data collection for evaluation. This is then reflected in missing evaluation plans, which in turn leads to lessons not being learned. To enhance the potential for knowledge generation and demonstration of impact, MHPPs should be more specific and contain measurable targets with allocated responsibilities and funding as well as evaluation plans.
Keywords: mental health plans and policies; public mental health; Mental Health Atlas; Europe; Ment al Health Action Plan 2013–2030